A dictionary of Shakespeare - Wells, Stanley W., 1930-; Shaw, James (Oxford : Oxford University Press, 2005)
"Compiled by the general editor of The Oxford Shakespeare, this dictionary includes hundreds of entries covering famous actors, writers, and directors connected with Shakespeare, as well as historical figures and places of particular interest. Ideal reference for the student, actor, or director, and fascinating browsing for the general reader." "The book includes passages on Shakespeare by famous authors, from Dr Johnson and Jane Austen to Bernard Levin and Virginia Woolf; intriguing details such as the proportion of verse and prose in each play, and the longest word Shakespeare used; and several appendices, including a chronology, as well as a list of characters and the plays in which they appear."--BOOK JACKET.
Previous ed.: 1998.
Title on cover and spine: Oxford dictionary of Shakespeare.
Includes bibliographical references.
Keywords: Shakespeare, William, -- 1564-1616 -- Dictionaries; Shakespeare, William, -- 1564-1616 -- Dictionnaires anglais